Pengaruh Literasi Keuangan dan Sikap Keuangan Terhadap Pengelolaan Keuangan pada Ibu Rumah Tangga Di Desa Telukan Kecamatan Grogol Kabupaten Sukoharjo - Patria Wirabhakti Wicaksono; Rina Susanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the Influence of Financial Literacy, Financial Attitudes on Financial Management of Housewives in Telukan Village. Data collection in this study used a questionnaire distributed to respondents. The sample in this study amounted to 100 respondents who were housewives in Telukan Village, Grogol District, Sukoharjo Regency with a sampling technique of Purposive sampling. The analysis method used in this study is the Classical Assumption Test, Descriptive Statistics, Multiple Linear Regression Analysis, T Test, Simultaneous Test (F), Determination Coefficient Test (R²).Based on the results of the t-test, the study shows that financial literacy has a significant effect on financial management, and financial attitudes have a significant effect on financial management. The results of the multiple linear regression analysis of this study are Y = 4.524 + 0.266 X1 + 0.312 X2 + e. The results of the F test show that the variables of financial literacy, financial attitudes have a significant effect simultaneously on financial management. The results obtained from the coefficient of determination (R²) are 0.558, meaning that the amount of contribution of the independent influence of X1 (Financial Literacy) and X2 (Financial Attitude) to Y (Financial Management) is 55.8%. The rest (100% - 55.8%) = 44.2% is influenced by variables not included in this study.